2018
DOI: 10.3389/fmicb.2018.00382
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Environment of blaTEM-1, blaCTX-M-15, blaCMY-42 and Characterization of Integrons of Escherichia coli Isolated From an Indian Urban Aquatic Environment

Abstract: The presence of antibiotic resistance genes (ARGs) including those expressing ESBLs and AmpC-β-lactamases in Escherichia coli inhabiting the aquatic environments is a serious health problem. The situation is further complicated by the fact that ARGs can be easily transferred among bacterial species with the help of mobile genetic elements – plasmids, integrons, insertion sequences (IS), and transposons. Therefore, the analysis of genetic environment and mobile genetic elements associated with ARGs is important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 61 publications
7
44
0
Order By: Relevance
“…Although the isolates in CTX-M-1 group were not identified any IS due to the short length of contigs (Figure 8B), most isolates in other groups, such as CMY-2, CTX-M-27, CTX-M-32, CTX-M-15, and CTX-M-55, carried IS1380 family insertion sequences in common, and the IS1380 element was located upstream of CTX-M and CMY-2 genes (Figures 8A,C,D). In particular, the isolates encoding CMY-2 gene harbored IS in the upstream and sugE gene in the downstream as previously reported (Singh et al, 2018). Furthermore, the set of tra genes related to conjugal transfer system was co-identified in the isolates with CMY-2 ( Figure 8A).…”
Section: Characterization Of Ctx-m and Cmy-2 Genes On E Colisupporting
confidence: 76%
“…Although the isolates in CTX-M-1 group were not identified any IS due to the short length of contigs (Figure 8B), most isolates in other groups, such as CMY-2, CTX-M-27, CTX-M-32, CTX-M-15, and CTX-M-55, carried IS1380 family insertion sequences in common, and the IS1380 element was located upstream of CTX-M and CMY-2 genes (Figures 8A,C,D). In particular, the isolates encoding CMY-2 gene harbored IS in the upstream and sugE gene in the downstream as previously reported (Singh et al, 2018). Furthermore, the set of tra genes related to conjugal transfer system was co-identified in the isolates with CMY-2 ( Figure 8A).…”
Section: Characterization Of Ctx-m and Cmy-2 Genes On E Colisupporting
confidence: 76%
“…In this study, 9 (52.9%) E. coli ST131 isolates transferred integron and resistance gene cassettes to E. coli J53 Az r by conjugation. Many previous studies found that most of the resistance determination and integron in E. coli were encoded in a transferable plasmid, which might be horizontally transferred to the isolates among E. coli ST131 or different bacteria species by conjugation, potentially resulting in multiple drug resistance of bacteria [36,37]. e result of PFGE demonstrated that integron-positive isolates were highly diverse in this study and there was no dominant clone ( Figure 1).…”
Section: Discussionmentioning
confidence: 54%
“…coli ST5377, ST361 and ST672 collected in India between 2012 and 2013 [ 20 ]. Studying its genetic environment, we observed upstream of the bla CMY-42 the two genes previously reported by Singh et al (2018) [ 21 ]: blc and sugE encoding for an outer membrane lipoprotein and a drug efflux pump, respectively. We additionally detected an intact IS Ecp1 upstream of bla CMY-42 , which was not as previously shown by Hentschke et al (2011) [ 22 ] disrupted by IS 1 .…”
Section: Discussionmentioning
confidence: 78%